Signaling Pathways Linked to Serotonin-Induced Superoxide Anion Production: A Physiological Role for Mitochondria in Pulmonary Arteries - Genet, Nafiisha; Billaud, Marie; Rossignol, Rodrigue; Dubois, Mathilde; Gillibert-Duplantier, Jennifer; Isakson, Brant E.; Marthan, Roger; Savineau, Jean-Pierre; Guibert, Christelle (Frontiers in Physiology, 2017)
Serotonin (5-HT) is a potent vasoconstrictor agonist and contributes to several vascular diseases including systemic or pulmonary hypertension and atherosclerosis. Although superoxide anion (O2•) is commonly associated to cellular damages due to O2• overproduction, we previously demonstrated that, in physiological conditions, O2• also participates to the 5-HT contraction in intrapulmonary arteries (IPA). Here, we focused on the signaling pathways leading to O2• production in response to 5-HT in rat IPA. Using electron paramagnetic resonance on rat IPA, we showed that 5-HT (100 µM)-induced O2• production was inhibited by ketanserin (1 µM - an inhibitor of the 5-HT2 receptor), absence of extracellular calcium, two blockers of voltage-independent calcium permeable channels (RHC80267 50 µM and LOE-908 10 µM) and a blocker of the mitochondrial complex I (rotenone – 100 nM). Depletion of calcium from the sarcoplasmic reticulum or nicardipine (1 µM – an inhibitor of the L-type voltage-dependent calcium channel) had no effect on the 5-HT-induced O2• production. O2• levels were also increased by -methyl-5-HT (10 µM - a 5-HT2 receptors agonist) whereas GR127935 (1 µM - an antagonist of the 5-HT1B/D receptor) and citalopram (1 µM - a 5-HT transporter inhibitor) had no effect on the 5-HT-induced O2• production. Peroxynitrites were increased in response to 5-HT (100 µM). In isolated pulmonary arterial smooth muscle cells loaded with rhod-2 or mitosox probes, we respectively showed that 5-HT increased both mitochondrial calcium and O2• levels, which were both abrogated in absence of extracellular calcium. Mitochondrial O2• levels were also abolished in the presence of rotenone (100 nM). In pulmonary arterial smooth muscle cells loaded with TMRM, we showed that 5-HT transiently depolarized the mitochondrial membrane whereas in the absence of extracellular calcium the mitochondrial membrane depolarisation was delayed and sustained in response to 5-HT. 5-HT decreased the mitochondrial respiratory rate measured with a Clark oxygen electrode. Altogether, in physiological conditions, 5-HT acts on 5-HT2 receptors and induces an O2• production dependent on extracellular calcium and mitochondria.